نظريـات ومبادئ تصميم الوسـائط المتعددة في تعليـم مفردات اللغة العربية وتعلمها :دراسـة تحليلية تقويمية - Nurkhamimi Zainuddin; Muhammad Sabri Sahrir (Universiti Sains Islam Malaysia, 2024)
This study attempts to analyze and evaluate theories and design principles for design and development of multimedia program for teaching and learning Arabic vocabulary. The researchers mentioned the research tools, research samples and steps which are related to the design and development process. The study proposes the implementation of social constructivism theory proposed by Vygotsky (1978), theory of second language acquisition by Krashen (1984), theory of multimedia learning by Mayer (2001) and ADDIE instructional model by Dick & Carey (1990). 4 subjects matter experts in teaching Arabic as a second language, syllabus design, computer assisted language learning and instructional technology had participated in the study. The outcome from this research will later be used by the researcher in the design and development processes of the multimedia program for teaching and learning Arabic vocabulary.